Pendampingan Komunitas Belajar dalam Penguatan Literasi Spiritual Masyarakat di Lampung Selatan - M Agus Kurniawan; Mustoto; Endar Evta Yuda Prayogi; Hajiri; Sucipto; Lina Marlina; Aulia Rahma (Bakti Masyarakat Pengabdian dan Pemberdayaan Masyarakat, 2026)
Spiritual literacy is a vital foundation for building dignified, cohesive communities rooted in Islamic values. This community service program aimed to develop a learning community mentoring model that integrates participatory approaches, local needs-based design, and spiritual literacy strengthening across five majelis taklim in South Lampung Regency, involving 400 community members, 200 religious leaders, and 150 majelis taklim administrators over eight months. Methods included regular mentoring, cadre training, interactive workshops, and individual guidance. Results showed a 113% increase in Quranic and Hadith literacy, 126% improvement in daily worship consistency, and 236% increase in majelis participation. Post-program evaluation indicated that 88% of participants applied spiritual values in daily life and 74% actively became literacy cadres in their communities. The program successfully established a sustainable spiritual learning ecosystem within majelis taklim communities, producing long-term impacts on sociospiritual well-being.